Exposure of Polish enterprises to risk within business cycle - Izabela Jonek-Kowalska (Managerial Economics)
In economies with relatively short free-market traditions, enterprises are highly exposed to general economic risk, including fluctuations in the business cycle, which may result in the limitation of their development opportunities and discourage them from undertaking business activity. Having regard to the aforementioned circumstances, the main goal of this article is to assess the exposure of Polish enterprises to the risk related to changes in the economic situa-tion. To achieve the goal set in such a manner, the first part of the article covers the grounds for the undertaken research along with an overview of the literature concerning the presented issues. In the second part of the article, the results of the risk assessment and the relationships of its level to the course of the business cycle in Poland during the years of 2000 to 2015 are shown. In the process of risk measurement, the statistical measures of variability and dynamics indices regarding the financial results of Polish enterprises are used. Whereas, in the course of determining the changes in the business cycle, the author makes use of the changes in the level of the Gross Domestic Product (GDP).